Increased phagocytic NADPH oxidase activity associates with coronary artery calcification in asymptomatic men. (3rd April 2017) - Beloqui, Oscar; Moreno, María U.; San José, Gorka; Pejenaute, Álvaro; Cortés, Adriana; Landecho, Manuel F.; Díez, Javier; Fortuño, Ana; Zalba, Guillermo
Abstract: Vascular calcification is a common feature in atherosclerosis and associates with cardiovascular events. Oxidative stress may be involved in the pathogenesis of vascular calcification. Previous studies have shown that the phagocytic NADPH oxidase is associated with atherosclerosis. The objective of the present study was to investigate the association between phagocytic NADPH oxidase-mediated superoxide production and coronary artery calcium (CAC). NADPH oxidase-mediated superoxide production was determined by chemiluminescence and CAC by computed tomography in 159 asymptomatic men free of overt clinical atherosclerosis. Multivariate linear regression analyses were used to assess the relationship between CAC and NADPH oxidase-mediated superoxide production. Compared with individuals in the lowest score of CAC (= 0 Agatston units), those in the upper score (>400 Agatston units) showed higher superoxide production ( p  < 0.05). In correlation analysis, superoxide production positively ( p  < 0.01) correlated with CAC, which in multivariate analysis remained significant after adjusting for age, HDL-cholesterol, triglycerides, body mass index, smoking, arterial hypertension and diabetes mellitus. In conclusion, in a population of men without clinically overt atherosclerotic disease, increased NADPH oxidase-mediated superoxide production associated with enhanced CAC. Albeit descriptive, these findings suggest a potential involvement of phagocytic NADPH oxidase-mediated oxidative stress in CAC.